Feasibility of Dose Escalation in Patients With Intracranial Pediatric Ependymoma - Tensaouti, Fatima; Ducassou, Anne; Chaltiel, Léonor; Bolle, Stéphanie; Habrand, Jean Louis; Alapetite, Claire; Coche-Dequeant, Bernard; Bernier, Valérie; Claude, Line; Carrie, Christian; Padovani, Laetitia; Muracciole, Xavier; et al. (Frontiers in Oncology, 2019)
Background and purpose: Pediatric ependymoma carries a dismal prognosis, mainly owing to local relapse within RT fields. The current prospective European approach is to increase the radiation dose with a sequential hypofractionated stereotactic boost. In this study, we assessed the possibility of using a simultaneous integrated boost (SIB), comparing VMAT vs. IMPT dose delivery. Material and methods: The cohort included 101 patients. The dose to planning target volume (PTV59.4) was 59.4/1.8 Gy, and the dose to SIB volume (PTV67.6) was 67.6/2.05 Gy. Gross tumor volume (GTV) was defined as the tumor bed plus residual tumor, clinical target volume (CTV59.4) was GTV + 5 mm, and PTV59.4 was CTV59.4 + 3 mm. PTV67.6 was GTV+ 3 mm. After treatment plan optimization, quality indices and doses to target volume and organs at risk (OARs) were extracted and compared with the standard radiation doses that were actually delivered (median = 59.4 Gy [50.4 59.4]). Results: In most cases, the proton treatment resulted in higher quality indices (p < 0.001). Compared with the doses that were initially delivered, mean, and maximum doses to some OARs were no higher with SIB VMAT, and significantly lower with protons (p < 0.001). In the case of posterior fossa tumor, there was a lower dose to the brainstem with protons, in terms of V59 Gy, mean, and near-maximum (D2%) doses. Conclusion: Dose escalation with intensity-modulated proton or photon SIB is feasible in some patients. This approach could be considered for children with unresectable residue or post-operative FLAIR abnormalities, particularly if they have supratentorial tumors. It should not be considered for infratentorial tumors encasing the brainstem or extending to the medulla.